2014
DOI: 10.1371/journal.pone.0087779
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health Related Quality of Life following Intensive Care during Treatment for Haematological Malignancies

Abstract: ObjectiveLong-term health-related quality of life (HRQoL) was determined for patients admitted to the haematology ward who needed intensive care treatment (H-IC+) and compared with those who did not (H-IC−) as well as with that for patients admitted to the general ICU (nH-IC+).MethodsA cross-sectional study was carried out median 18 months after admission by employing the short form-36, checklist for individual strength, cognitive failure questionnaire and hospital anxiety and depression scale.Results27 (79%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 26 publications
(29 reference statements)
2
41
0
Order By: Relevance
“…As the longer term psychological and physical impact of intensive care on those surviving acute critical illness is increasingly documented, the patients and their relatives need to be prepared for challenges that can occur after discharge from the ICU. However, a growing body of evidence indicates that long‐term reductions in quality of life are not necessary and that some patients can benefit from intensive care treatment without the fear of long‐term sequelae …”
Section: Transitioning To End‐of‐life Carementioning
confidence: 99%
“…As the longer term psychological and physical impact of intensive care on those surviving acute critical illness is increasingly documented, the patients and their relatives need to be prepared for challenges that can occur after discharge from the ICU. However, a growing body of evidence indicates that long‐term reductions in quality of life are not necessary and that some patients can benefit from intensive care treatment without the fear of long‐term sequelae …”
Section: Transitioning To End‐of‐life Carementioning
confidence: 99%
“…This was similar to patients who never required intensive care [76]. van Vliet et al [79] also showed that admission to the ICU had no negative impact on long-term healthrelated quality of life for patients being treated for a hematologic malignancy. Forty-five percent (45%) of the patients in the study were recipients of HSCT.…”
Section: End Of Life Issues In Hsct Patientsmentioning
confidence: 60%
“…Twenty‐three studies were identified extensively reporting the measurement/psychometric properties for the EORTC‐QLQ‐C30 general oncology measure, followed by EORTC‐MY24 module and SF‐36 generic measure . Most of the studies provided evidences for internal consistency, convergent/divergent validity, floor/ceiling effect and responsiveness.…”
Section: Resultsmentioning
confidence: 99%